2012
DOI: 10.1093/jjco/hys076
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction in Patients Treated with Tyrosine Kinase Inhibitors, Sunitinib, Sorafenib and Axitinib, for Metastatic Renal Cell Carcinoma

Abstract: Patients treated with the tyrosine kinase inhibitors developed thyroid dysfunction frequently. Furthermore, those treated with axitinib developed thyroid dysfunction significantly more and at a faster rate than the others. Therefore, when the tyrosine kinase inhibitors, especially axitinib, are used, close monitoring of thyroid function is recommended, at least for the initial 1-2 months, to avoid clinical symptoms derived from thyroid dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 18 publications
2
18
0
1
Order By: Relevance
“…A transient decrease in TSH, suggesting a thyroiditis-induced thyrotoxic phase, was also identified in some of their patients. Several subsequent studies have confirmed a high frequency of axitinib-related thyroid dysfunction, ranging from 88% to 100% (2,7,8). Consistent with earlier reports, the six patients reported here developed thyroid dysfunction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A transient decrease in TSH, suggesting a thyroiditis-induced thyrotoxic phase, was also identified in some of their patients. Several subsequent studies have confirmed a high frequency of axitinib-related thyroid dysfunction, ranging from 88% to 100% (2,7,8). Consistent with earlier reports, the six patients reported here developed thyroid dysfunction.…”
Section: Discussionsupporting
confidence: 91%
“…Thyroid dysfunction has also been described with other antiangiogenic agents, such as sorafenib and sunitinib, although at lower rates (1,3,8). In this study, the relationship between TSH and thyroid hormone levels was also evaluated in patients treated with sunitinib and sorafenib; the results showed a weaker tendency compared to the axitinib-treated patients.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In a phase I/II trial, up to 89% patients showed increased TSH level [15]. Another study reported that the risk of hypothyroidism was higher for axitinib than for sorafenib and sunitinib (HR 4.53, p = 0.01) [16]. As the frequency and timing of hypothyroidism may differ for each TKI, TKIs should be considered individually.…”
Section: Discussionmentioning
confidence: 99%
“…45 In terms of thyroid dysfunction, a Japanese study observed that mRCC patients treated with axitinib developed incident thyroid dysfunction more commonly and within a shorter time frame when compared to those treated with sorafenib or sunitinib. 46 However, these findings were limited by the small retrospective nature of the study. Nevertheless, these findings together highlight the important toxicity considerations and clinical monitoring necessary while using axitinib.…”
mentioning
confidence: 93%